An Analysis Operational of Strategic Plan Based on Balance Score Card Perspective with Hospital Performance in Pabatu Hospital, Tebing Tinggi City 2021 - Siti Hapsah Panjaitan; Erni Girsang; Sri Lestari Ramadhan Nasution; Sri Wahyuni Nasution (Budapest International Research and Critics University, 2022)
Performance appraisal using the Balanced Scorecard method comprehensively measure hospital performance from both the financial and non-financial sectors. As a health service company, it must have a comprehensive, coherent, balanced and measurable performance appraisal system. This study aims to analyze, test, and measure hospital performance using the Balanced Scorecard case study at Pabatu General Hospital. The problem is the research is formulated as follows: how is the performance of the Pabatu General Hospital for the 2018-2020 period based on the Balanced Scorecard. The assessment is carried out from four perspectives, namely financial perspective, customer perspective, internal business perspective, and growth and learning perspective. Hospital performance from the customer perspective in 2018-2020 for the percentage of customer retention is still not good, customer acquisition has been very good and customer satisfaction is quite good. Performance from an internal business perspective in 2018 – 2020 is not good where the percentage values of BOR, BTO, and TOI, are not by the standards of the Ministry of Health. Performance from the perspective of growth and learning at Pabatu General Hospital in 2018-2020 shows a fairly good percentage.